DETERMINING THE MARKETING STRATEGY OF STIE MAHAPUTRA RIAU USING THE K-MEANS CLUSTERING ALGORITHM METHOD - Rahmadani Hidayat; Sarjon Defit; Menhard Menhard (Jurnal Apresiasi Ekonomi, 2024)
The difficulty of getting new prospective students requires STIE Mahaputra Riau to be able to design an effective and efficient marketing strategy. This study aims to determine a marketing strategy using the K-Means Clustering method. The K-Means Clustering algorithm method is to cluster data based on the attributes of student name, school of origin, area of origin and chosen study program, so that cluster data output is obtained that can be used in making marketing strategy decisions. The sample data used in this study are data from high school, vocational high school or equivalent students who are in the third grade in 2023, specifically for the province of Riau and its surroundings, totaling 750 data. The results of this study indicate that based on the total student data of 750 people, they are grouped into 3 clusters. Cluster 1 consists of 145 people from Rokan Hulu, Indragiri Hilir, Bengkalis, Kuantansingingi and West Sumatra Regencies. Cluster 2 consists of 344 people from Kampar and Indragiri Hulu Regencies. And cluster 3 as many as 261 people from Pelalawan, Siak and Rokan Hilir Regencies. It was also found in each cluster, the study program with the most interest was the S1 Management study program. So the marketing strategy implemented should pay attention to the area of origin and the study program chosen as the basis for implementing policies in accepting new prospective students.Keywords : Data Mining, Marketing Strategy, Clustering, K-Means Method